PENANGANAN SAMPAH ORGANIK DENGAN BAK SAMPAH KOMPOSTER DI DUSUN SUSUKAN KELURAHAN SUSUKAN KECAMATAN SUSUKAN KABUPATEN SEMARANG - Nur Aklis; Masyrukan Masyrukan (WARTA LPM, 2016)
Not properly managed of garbage will impact the health, social and economic. It occurs in RT 03, RT 04 RW 1, Susukan Village, Semarang District. Most residents of both RT are still throwing garbage in any place, and others make puddles for landfills. This paper addresses the issue of handling organic waste from the initially discarded in places and wallow carelessly processed into compost and liquid fertilizer in a composter in Susukan Village , District of Semarang. The activities begins with making management team that are divided according to their respective RT, provision of trash for inorganic waste, manufacture and operation of the composter training for the management team, training provision and operation of the composter for residents. The results of activities undertaken resident of RT 03 RW 04 has a system to manage garbage, produce fertilizer so the impact on improving the quality of health and social citizens.